O ser docente e o tempo: relação entre o tempo de docência e os processos de prazer e sofrimento no trabalho do professor da Secretaria Municipal de Educação de Santos - Marques, Ana Cláudia Sierra [UNIFESP] (2017)
The main environment of the teaching practice is the school, where this study is built. The studies investigate the relation between the career time and the processes of sufferings and pleasure of the teachers, besides a certain analysis of the occupational stress generated, going into the aspects related to the work organization and the teaching career. Working with the richness of the field of Work - related Mental Health, the research is based on the conceptual framework of Stress Theory and Burnout, but includes the proposition of constructs created from the concepts of pleasure and suffering, extracted from the psychodynamic theory of job. The aim of this research is to find grounds for the construction of action / reflection in favor of the professional exercise, as well as to deal with the teaching being, in face of the demands of the work organization, the experiences lived during the career, and the relations of these factors with the perceptions Of stress, suffering and pleasure at work expressed by the subjects. It is a field study, descriptive, transversal, articulating quantitative and comprehensive-interpretative methods. The procedure was the direct request of information to teachers of the Department of Education of Santos, in teaching activity, about the hypothesis, which affirmed, the longer the career time, the greater the suffering and the stress. The data collection was done with a selfadministered questionnaire, created for this purpose, containing 32 direct questions, 24 of which were multiple choice and 8 were open. The topics discussed are related to the main variable, teaching career time, as well as recognition, appreciation, pleasure and suffering at work. In two questions, the technique of free association of words, differential of the instrument was used because it places the subject in a more subjective reflection in the contact with the motives and feelings in relation to his profession. The non-probabilistic sample consisted of 115 teachers who accepted an invitation to participate in the study, after approval of the Education Department of Santos. Data were analyzed from relative frequencies and inferential analyzes. The degree of suffering and pleasure were measured on a scale of 0 to 10, and presented complementary means: 4.42 for the degree of suffering and 6.76 for the degree of pleasure. Another highlight is the words expressed by the subjects, where dedication, commitment, fulfillment, vocation, love, fatigue, which formed the clouds of words, an analyzer of frequencies. The final product, was conceived and created, from the results, with a playful character. It is a game that can be used with the teachers, in a itinerant way in the spaces of permanent education, enabling the work with the questions raised in this research on the teaching career. It seeks to bring lightness to work, even dealing with the experiences associated with career time and the experiences of pleasure and suffering at work. This initiative aims to contribute to the well-being of teachers and so that the municipality can become a reference in the treatment of the theme.